2008
DOI: 10.1007/s00210-008-0279-6
|View full text |Cite
|
Sign up to set email alerts
|

ATP-binding cassette transporters in human heart failure

Abstract: Adenosine triphosphate-binding cassette (ABC) transporters are involved in energy-dependent transport of substrates across biological membranes. We hypothesized that their expression is altered during human heart failure, suggesting a pathophysiologic basis. Messenger ribonucleic acid quantification of all known ABC transporters revealed multiple alterations in ABC transporter expression in failing human hearts (New York Heart Association classification III-IV) compared to nonfailing controls. These include a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 36 publications
4
30
0
Order By: Relevance
“…For rosiglitazone it has recently been demonstrated that it is a substrate of BCRP and can also inhibit this transporter with a half-maximal inhibitory concentration (IC) 50 value of 25 mol/l [16] . Moreover, troglitazone sulfate, the major metabolite of troglitazone, was identified as a BCRP substrate [17] , and troglitazone and rosiglitazone can induce BCRP [18] .…”
Section: Glitazones and Abc Transportersmentioning
confidence: 99%
“…For rosiglitazone it has recently been demonstrated that it is a substrate of BCRP and can also inhibit this transporter with a half-maximal inhibitory concentration (IC) 50 value of 25 mol/l [16] . Moreover, troglitazone sulfate, the major metabolite of troglitazone, was identified as a BCRP substrate [17] , and troglitazone and rosiglitazone can induce BCRP [18] .…”
Section: Glitazones and Abc Transportersmentioning
confidence: 99%
“…Transport assays were performed as described previously (Solbach et al, 2008;Zolk et al, 2009 (Zolk et al, 2009). These potential inhibitors were selected based on previous publications suggesting them as substrates/inhibitors of OCT2 and/or on the presence of physicochemical characteristics generally associated with OCT2 substrates/ inhibitors, such as net positive charge at the amine nitrogen at physiological pH and molecular weight Ͻ500.…”
mentioning
confidence: 99%
“…BCRP is localized at endothelial cells and cardiomyocytes in heart (Meissner et al, 2006;Solbach et al, 2008). It is not clear whether this localization of BCRP in heart tissue is well reflected in the currently used tissue-slice method because the tissue surface might be exposed to the drug solution directly, and BCRP may not be able to exclude donepezil as efficiently as it would in its role as a tissue barrier transporter in intact tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to P-glycoprotein, BCRP is also expressed in heart, mainly in capillary endothelial cells and cardiomyocytes (Meissner et al, 2006;Solbach et al, 2008;Higashikuni et al, 2010;Emmert et al, 2013), so BCRP is also a potential site of DDI. However, it has not been reported whether donepezil is a substrate of BCRP.…”
Section: Introductionmentioning
confidence: 99%